Gambaran Tingkat Pengetahuan Remaja Putri Tentang Vulva Hygiene di Pondok Pesantren Budi Utomo Surakarta - Novia Nur Hanifah (Yayasan Literasi Sains Indonesia, 2022)
Vulva Hygiene is maintaining the cleanliness of the external genital organs. The benefits of vulvar hygiene are to keep the vagina clean, to comfort the vagina while traveling and to avoid problems such as vaginal discharge, vulvar pruritus and other reproductive tract infections. This study was conducted to identify a description of knowledge, age and education related to vulvar hygiene in adolescent female. This study used descriptive research method and the research subject is the population of adolescent female at the Budi Utomo Islamic Boarding School, Surakarta. The results from 207 respondents showed the majority aged 16-18 years old (intermediate phase) as many as 89 respondents (43%), the education level of the majority were adolescent female who had graduated from high school and continued to stay in as many as 55 respondents (26.6%), the level of knowledge of vulva hygiene is mostly less as many as 113 respondents (54.6%). Most of the adolescent female in the Budi Utomo Islamic Boarding School Surakarta have less knowledge about vulva hygiene. This study distributed questionnaires to adolescent female aged 14-21 years old to find out the knowledge of adolescent female about vulvar hygiene in order to avoid various reproductive health issues.